Integration of a Glutamate Sensitive Genetically Encoded Sensor Protein into Photocrosslinkable Hydrogel Optrodes. Issue 8 (2016) - Kahyaoglu, Leyla N.; Rickus, Jenna L.
ABSTRACT: Immobilization into 3D matrices stabilizes proteins in comparison to flat planar surfaces and facilitates the study of the biomolecular interactions as well as integration into optrodes for cell physiology. Photocrosslinkable hydrogels have received significant attention in recent years as they provide not only a highly hydrophilic 3D environment to promote protein stabilization and its interactions with analyte molecules, but enable optically addressable patterning for spatial control of protein localization. At the same time, the explosion of new genetically encoded sensor proteins has greatly expanded the range of optical molecular sensors for cell physiology. Here we integrate a genetically encoded glutamate sensor protein into a photocrosslinkable hydrogel via covalent interaction to create a novel glutamate sensor material. Protein immobilization can be achieved through covalent bonds, physical interactions, or physical entrapment. Although physical entrapment without chemical modifications offers a universal approach for protein immobilization, leaching of protein through the pores of the hydrogel is a significant challenge. Thus, here an alternative method is developed to provide better control of protein localization and immobilization using naturally existing reactive groups of proteins. To this end, a genetically encoded FRET based glutamate indicator protein (FLIPE) is modified with diacrylated poly (ethylene glycol) (PEGDA) by Michael-type addition between acrylate groups and the thiol side chains of the cysteine residues. We optimize the molecular weight of PEGDA (300, 740, and 3400 Da) as well as concentrations of the photoinitiator (0.1, 0.5 and 1 % (w/w)) and monomer (10, 20, and 30 % (w/w)) in the precursor solution. Next the precursor solution is grown at the distal end of an optical fiber to test the spectroscopic properties and characteristic bioactivities of proteins in the hydrogel network. Optimization of the irradiation parameters, light intensity and exposure time, improves the spatial resolution of 3D hydrogel tips. This study examines the capability of fabricating 3D hydrogel sensors covalently modified with a member of recently growing genetically encoded fluorescent biosensors, which can later be extended to all conformation-dependent protein biosensors and be used intracellularly for physiological and biological sensing purposes.